PROBLEMS OF LINGUISTIC AND METHODS OF TEACHING A FOREIGN LANGUAGE - Norjon Gafurova; Artikova Sarvinoz (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article deals with the problem of intercultural communication, in which background knowledge plays an important role. Referring to our research, we see the solution to this problem in expanding the background knowledge of students, i.e. familiarization of students with the realities, traditions and customs of English-speaking countries.